Comparative Study on Cognitive Development of Children Enrolled in Public and Private Pre-Schools of Karachi - Bano, Syeda Samana; Irfan , Nighat (Nurture, 2016)
Initial years of schooling experiences are an important influencer of cognitive development. In Pakistan children, parents and employers face many issues due to vast differences in standards of private and public schools. The purpose of this research is to study and compare the cognitive development of children age 4 to 5 years enrolled in public and private pre-schools (25 from each type) of Karachi. Children were given various tasks to assess their cognitive performance and on the basis of this performance were categories as having high or low cognitive performance. Cognitive performance of private school children was significantly better than that of children form public schools overall and in all tasks. Among public school 64 % and among private school 100% had good cognitive performance (P<0.05). These observations indicate a need for exploring the reasons and taking actions to rectify the situation.